Itäisen suomen ja venäjän liiketaloudellisen yhteistyön mahdollisuudet - Hannu Hernesniemi; Kati Järvi; Jari Jumpponen; Grigori Dudarev; Tauno Tiusanen (The Research Institute of the Finnish Economy (ETLA), 2005)
Selvitys käsittelee itäisen Suomen ja Luoteis-Venäjän liiketoiminnallisen yhteistyön mahdollisuuksia. Itäinen Suomi käsittää tässä viisi maakuntaa: Etelä- ja Pohjois-Savon, Etelä- ja Pohjois- – – This study looks at the possibilities of increasing business activity between Eastern Finland and Northwest Russia. Eastern Finland here consists of five regions: South and North Savo, South and North Karelia and Kainuu. The population of these regions totals 800,000. Agriculture, forestry and food products manufacturing are the regions' most important industries. They are also industries in which regional manufacturers are highly competitive. Because of the forest industry's strong position, manufacturers in these regions are relatively export oriented, but mostly to the western market and not to Russia. Exports to Russia usually originate from other parts of Finland. Over-the-border networking will impart a strong impact on the economy of Eastern Finland. Northwest Russia is the home to over 14 million inhabitants. The most important urban area is St. Petersburg and the surrounding Leningrad region. For Eastern Finland, the bordering Republic of Karelia is also an important source of business. Finland is also the nearest foreign country to Nenetsia and Komi, which have rich oil and gas resources, the Archangel region, where activity is heavily concentrated in the forest industry, and the steel industry center of Vologda. For developing economic integration, we propose economic zones comprised of cross-border twin cities, over-the-border co-operation in education and research, as well as investment in infrastructure to support business activity. Finnish small and medium-sized companies should expand to Russia to provide subcontracting services. Due to the importance of transit trade, it would also be beneficial to form a logistics centre connecting over-the-border transit hubs. Russian tourists and immigrants who establish businesses in Finland provide remarkable resources for Eastern Finland. The biggest potential gains from economic co-operation would be in those industries in which Eastern Finland has a competitive edge, namely the forest industry and related activities and possibly in food products manufacturing.
Keywords: 330; Eastern Finland; Northwest Russia; economic cooperation; over-the-border networking; Handelsregionalismus; Russland (Nord); Finnland